Desktop aligner for fabrication of multilayer microfluidic devices - Li, Xiang (Rev Sci Instrum, 2015)
Multilayer assembly is a commonly used technique to construct multilayer polydimethylsiloxane (PDMS)-based microfluidic devices with complex 3D architecture and connectivity for large-scale microfluidic integration. Accurate alignment of structure features on different PDMS layers before their permanent bonding is critical in determining the yield and quality of assembled multilayer microfluidic devices. Herein, we report a custom-built desktop aligner capable of both local and global alignments of PDMS layers covering a broad size range. Two digital microscopes were incorporated into the aligner design to allow accurate global alignment of PDMS structures up to 4 in. in diameter. Both local and global alignment accuracies of the desktop aligner were determined to be about 20 μm cm(−1). To demonstrate its utility for fabrication of integrated multilayer PDMS microfluidic devices, we applied the desktop aligner to achieve accurate alignment of different functional PDMS layers in multilayer microfluidics including an organs-on-chips device as well as a microfluidic device integrated with vertical passages connecting channels located in different PDMS layers. Owing to its convenient operation, high accuracy, low cost, light weight, and portability, the desktop aligner is useful for microfluidic researchers to achieve rapid and accurate alignment for generating multilayer PDMS microfluidic devices.